In silico and ADME-T prediction of amygdalin as an anticancer agent against CDK-2 in colon cancer - Prajapati, Mahendra (Philippine Journal of Science, 2024)
Colorectal cancer (CRC) poses a significant public health issue nowadays. Chemotherapeutic drugs – including 5-fluorouracil, capecitabine, doxorubicin, and paclitaxel – effectively stop the development of malignant cells. However, these drugs affect healthy cells and have numerous side effects. The present study employed the computational molecular docking method and ADME-T analysis of the selected herbal anticancer compound (amygdalin) against colon cancer. Molecular docking analysis was performed using the Schrödinger Suite against the CDK-2 protein. In addition, an ADME-T analysis was performed for amygdalin to evaluate the physicochemical, pharmacokinetic, and pharmacodynamic properties using Protox III, pkCSM, and the SwissADME web server. The results showed that amygdalin has a maximum binding affinity (–10.92 kcal/mol) toward the target protein CDK-2. ADME-T analysis suggests that amygdalin may be a potential chemotherapeutic agent for CRC. Amygdalin had no carcinogenicity and genotoxicity and had low acute oral toxicity when administered orally. This study will help the scientific community and society to identify therapeutically effective agents for the treatment of CRC.